Coreopsis leavenworthii - Edward F. Gilman; Jeffrey G. Norcini; Teresa Howe (EDIS)
Thirteen Coreopsis species occur in Florida, eleven of which are widely considered native to Florida. Coreopsis leavenworthii is found throughout Florida, and until recently was considered endemic. It is an annual to short-lived perennial. These colorful plants have pinnately to bipinnately compound leaves. In cultivation, this species has more foliage than what would normally be seen in the wild. This document is Fact Sheet FPS-142, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: October 1999. Revised November 2003.